The relationship between length of illness and quality of life in patients with colorectal cancer - Rupang, Ernita Rante; Nursalam, Nursalam; Sembiring, Friska (Gaceta Médica de Caracas, 2024)
Introduction: The length of illness often results in changes in the quality of life of colorectal cancer patients in several aspects of life, such as psychological, physiological, and social, especially the initial condition of the patient diagnosed. Due to the high risk of death from colorectal cancer, it is recommended that the timing of diagnosis be important for all colorectal cancer patients. The aim was to determine the relationship between length of illness and quality of life in colorectal cancer patients. Methods: The research method uses a correlational design with a cross-sectional approach. The sampling method is purposive sampling, with a sample size of 72 patients. The research variables are the length of illness and quality of life. The research instrument is the WHOQOL-BREF questionnaire.